Effects of Childhood Polyvictimization on Victimization in Juvenile Correctional Facilities: The Mediating Role of Trauma Symptomatology. (April 2019) - Yoder, Jamie R.; Hodge, Ashleigh I.; Ruch, Donna; Dillard, Rebecca
Polyvictimization refers to multiple forms of victimization experienced by youths. The extent to which aggregated or cumulative early life victimization increases risk of victimization within juvenile correctional facilities is unclear. Furthermore, pathways from early polyvictimization to facility victimization may be partly explained by trauma symptomatology. Drawing upon the extant polyvictimization literature, this study explores both composite and cumulative effects of childhood victimization on later victimization within correctional facilities and the mediating role of trauma symptomatology among a nationally representative sample of incarcerated youth. Data were drawn from the Survey of Youth in Residential Placement. Incarcerated youths ( N = 7, 073) were surveyed on constructs including early victimization, trauma symptomatology, and experiences of victimization within correctional facilities. Using appropriate weights in analyses, structural equation models revealed the relationship between amassed early polyvictimization and composite facility victimization was partially explained by trauma symptoms; facility victimization also linked to trauma symptoms. Additional models revealed that as youths report more victimization experiences, there was a successive increased likelihood for trauma symptoms, facility robbery, and facility physical victimization. The relationships between cumulative early victimization and facility robbery, physical, and sexual victimization were partially or fully mediated by trauma symptoms. Research and practice implications are discussed.